Spherical Silver Nanoparticles in the Detection of Thermally Denatured Collagens - Ahumada-Escandon, M; Ahumada-Escandon, M (Springer Verlag, 2016)
We have developed a rapid colorimetric method to determine the concentration of denatured collagen in solution, which is based on the collagen-silver nanoparticle corona formation. Using the proposed method, the lowest detectable concentration of denatured collagen protein in a solution of pure collagen was 14.7, 8.5, and 8.6 μg mL-1 for porcine (PCOL), rat tail (RCOL), and type I human recombinant (HCOL) collagen, respectively. © 2016 Springer-Verlag Berlin Heidelberg.
Keywords: Collagen; Nanoparticles/Nanotechnology; Surface plasmon band